2-(2-indolyl-)-4(3H)-quinazolines derivates as new inhibitors of AChE: design, synthesis, biological evaluation and molecular modelling. (June 2013) - Li, Zeng; Wang, Bin; Hou, Jin-Qiang; Huang, Shi-Liang; Ou, Tian-Miao; Tan, Jia-Heng; An, Lin-Kun; Li, Ding; Gu, Lian-Quan; Huang, Zhi-Shu
<x xml:space="preserve">Abstract</x> We recently reported that synthetic derivatives of rutaecarpine alkaloid exhibited high acetyl cholinesterase (AChE) inhibitory activity and high selectivity for AChE over butyrylcholinesterases (BuChE). To explore novel effective drugs for the treatment of Alzheimer's disease (AD), in this paper, further research results were presented. Starting from a structure-based drug design, a series of novel 2-(2-indolyl-)-4(3H)-quinazolines derivates were designed and synthesized as the ring-opened analogues of rutaecarpine alkaloid and subjected to pharmacological evaluation as AChE inhibitors. Among them, derivates 3a–c and 3g–h exhibited strong inhibitory activity for AChE and high selectivity for AChE over BuChE. The structure–activity relationships were discussed and their binding conformation and simultaneous interactions mode were further clarified by kinetic characterization and the molecular docking studies.